PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID UNTUK MATA KULIAH BULU TANGKIS - Kurniawan, Wawan; Kresnadi, Hery; Triansyah, Andika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to develop android-based learning media for badminton courses and know the validity, effectiveness and responses of students to the learning media. This research was conducted in Penjaskesrek Study Program of Tanjungpura University Pontianak with research subject of student of 4th semester of academic year 2016/2017. The research method used is the ADDIE development model which consists of Analiysis (Analysis), Design (Design), Development (Development), Implementation (Implementation), and Evaluation (Evaluation). The results showed that the prevalence rate of android based learning media for badminton subject based on expert material judgment obtained score 45 with percentage 81.81% which included in criterion of very valid and expert media judgment obtained score 70 with percentage 73.68% which included in criterion of quite valid. The effectiveness of this learning media amounted to 1.09 which is large, so the learning media was used effectively. Students' responses to learning media based on android for badminton course give positive responses with average score percentage equal to 84.79%.Â Keywords: Research and Development, Learning Media, Android, BadmintonÂ